Negative effects of lifespan extending intervention on resilience in mice. - Katelynn M Corder; Jessica M Hoffman; Anamarija Sogorovic; Youfeng Yang; Anisha Banerjee; Yi Sun; Michael B Stout; Steven N Austad (PLoS ONE)
One key goal of basic aging research is the development of reliable assays of both current and future health. These assays could dramatically accelerate progress toward developing health-extending interventions by obviating the need for full lifespan studies, especially if they were informative relatively early in life. One potential approach is the assessment of physiological resilience, defined as the ability to recover from an adverse event. Here, using CB6F1 mice, we evaluated four potential resilience assays, each quantifying recovery from a physiological challenge with clear relevance to humans. The challenges were: (1) anesthesia recovery, (2) restoration of hemoglobin levels after a blood draw, (3) speed of wound healing, and (4) survival after pathogen exposure. We evaluated how each changed with age and with interventions known to extend health in males only (17α-estradiol) or both sexes (calorie restriction). We found that three of the four (recovery from anesthesia, blood draw, and pathogen exposure) showed significant and expected age effects, but wound healing did not. None of the three age-sensitive assays responded to the health-extending interventions in the way we expected, and for some assays, including anesthesia response, interventions actually worsened outcomes. Possible explanations are: (1) our interventions were too brief, (2) the ages we evaluated were too young, (3) our assays did not capture important features of organismal resilience, or (4) organismal resilience is not as clearly related to current or future health as hypothesized. Future studies are needed to determine which of these interpretations is valid and to determine whether other resilience metrics may be more informative about current and future health.